Sport Climbing and Bouldering - Injury Patterns with Focus on the Lower Extremities - Obcowska, Alicja; Duda, Joanna; Kędzia, Jakub; Walendzik, Aleksandra; Racisz, Paweł; Obcowska, Kinga; Racisz, Kinga (Quality in Sport, 2025)
Introduction Climbing has grown significantly in popularity and includes various sub-disciplines that differ in environment, equipment, and injury patterns. A key distinction lies between sport climbing, which uses ropes, and bouldering, where only crash pads are used. That leads to different injury risks. While lead climbing injuries often affect the upper limbs, bouldering more commonly results in lower limb injuries like sprains and strains. Given the specificity and potential long-term consequences of these injuries, raising awareness and developing targeted prevention and rehabilitation strategies is crucial. Aim of study This study aims to review the current literature on climbing-related injuries with a focus on lower limb injuries, especially knee injuries, and provide an overview of potential prevention and treatment strategies. Materials and methods The literature was sourced from databases like PubMed, Google Scholar, and other relevant platforms using search terms such as ‘bouldering’, ‘sport climbing’, ‘injuries’, ‘lower limb injuries’, and ‘strategies’. The review focused on English-language articles published from 2015 onward. Conclusion Climbing-related injuries are becoming increasingly common, yet research on lower limb injuries remains limited. This makes it difficult to define clear prevention and rehabilitation strategies. Raising awareness of injury risks and applying standard treatment approaches based on accurate diagnosis is essential